Prevalence of Teenage Pregnancy in A Community Hospital of Rural Nepal: A Cross-sectional Study - Muna Maharjan (2019)
© 2019 Journal of Nepal Medical Association. All rights reserved. Introduction: Teenage pregnancy is a public health concern. Maternal and neonatal health outcomes are negatively impacted in teenage pregnancy. The objective of the study is to find the prevalence of teenage pregnancy in a community hospital of rural Nepal. Methods: A descriptive cross-sectional study was conducted at Okhaldhunga Community Hospital, Okhaldhunga, Nepal. Ethical approval was taken from the Institutional Review Committee of the hospital. Data were retrieved from July 2007 to July 2017 from the hospital record books. The total of 7054 records of deliveries were reviewed from the hospital records and whole sampling was done. Subgroup analysis was done on basis of age, ethnicity, gravida, para, period of gestation, mode of delivery, maternal or neonatal complications and birth weight. Data entry was done in Microsoft Excel and point estimate at 95% CI was calculated along with frequancy and proportion for binary data. Results: The total of 7054 deliveries were conducted in ten years among which 2050 (29.06%) were teenage deliveries at the 95% CI (28.52 to 29.06). The highest percentage of teenage delivery was found among Janajati ethnicity of 1056 (53.3%). Amongst teenage delivery, a significant tear was found in 157 (7.9%) as a maternal complication. Perinatal deaths were found in 27 (1.4%). Conclusions: The trend of teenage pregnancy remains almost same over ten years in the Okhaldhunga Community Hospital. The overall prevalence of teenage delivery is higher than the national figure. Low birth weight babies, premature delivery, perineal and cervical tears were the common complications. Further health education and awareness programs might help to reduce the teenage pregnancy rate.